The Influence of Self Leadership, Work Ability, Organizational Climate on Teacher Burnout and Performance at SMAN 12 Surabaya - Charles H. Sidauruk; Ida Aju Brahmasari; Ida Aju Brahma Ratih (ePaper Bisnis : International Journal of Entrepreneurship and Management, 2025)
SMA Negeri 12 Surabaya (SMAN 12 Surabaya), known as "SMANDALAS," was established in 1982. Initially, learning activities were carried out in the SDN Pakal 1 No. 119 building, Benowo, for one year while waiting for the construction of the permanent building to be completed. The new building began to be used on December 9, 1983, in accordance with the Decree of the Minister of Education and Culture No. 377/104.1.1/E5.83/SK. Currently, SMAN 12 Surabaya is located at Jl. Sememi Kidul No. 1, Benowo District, West Surabaya. This school has a land area of approximately 30,000 m² and is equipped with various facilities to support learning activities both inside and outside the classroom such as classrooms, laboratories, libraries, mosques, playgrounds, school forests, school gardens, ceremonial fields, sports fields, green open spaces, art rooms and others. This school is also equipped with adequate bathroom facilities for all school residents, a health unit room, meeting room, hall, green house, fish pond, fish pond and school garden. MAN 12 has achieved many achievements in both academic and non-academic fields. This is inseparable from the good cooperation between school leaders, teachers, employees, students and guardians. Every leader who leads at SMAN 12 Surabaya has a program that supports the achievements of students and teachers. In 2025, SMAN 12 Surabaya will become a pilot project for the "Food School Care" program as an implementation to support the national food security program. The purpose of this study was to determine the effect of Self Leadership, Work Ability, Organizational Climate on Burnout and Teacher Performance at SMAN 12 Surabaya. This study uses a quantitative method with primary data sources obtained from distributing questionnaires. The population of the study were teachers at SMAN 12 Surabaya. The selection of respondents was carried out using the saturated non-probability sampling method with a total of 74 respondents. The data analysis method used descriptive analysis and SEM-PLS analysis. The results of the study showed that the variables of self-leadership, work ability, and organizational climate had an effect on burnout and teacher performance at SMAN 12 Surabaya.